Making sense of joint commissioning: three discourses of prevention, empowerment and efficiency - Dickinson, Helen (BioMed Central, 2013)
BACKGROUND: In recent years joint commissioning has assumed an important place in the policy and practice of English health and social care. Yet, despite much being claimed for this way of working there is a lack of evidence to demonstrate the outcomes of joint commissioning. This paper examines the types of impacts that have been claimed for joint commissioning within the literature. METHOD: The paper reviews the extant literature concerning joint commissioning employing an interpretive schema to examine the different meanings afforded to this concept. The paper reviews over 100 documents that discuss joint commissioning, adopting an interpretive approach which sought to identify a series of discourses, each of which view the processes and outcomes of joint commissioning differently. RESULTS: This paper finds that although much has been written about joint commissioning there is little evidence to link it to changes in outcomes. Much of the evidence base focuses on the processes of joint commissioning and few studies have systematically studied the outcomes of this way of working. Further, there does not appear to be one single definition of joint commissioning and it is used in a variety of different ways across health and social care. The paper identifies three dominant discourses of joint commissioning – prevention, empowerment and efficiency. Each of these offers a different way of seeing joint commissioning and suggests that it should achieve different aims. CONCLUSIONS: There is a lack of clarity not only in terms of what joint commissioning has been demonstrated to achieve but even in terms of what it should achieve. Joint commissioning is far from a clear concept with a number of different potential meanings. Although this ambiguity can be helpful in some ways in the sense that it can bring together disparate groups, for example, if joint commissioning is to be delivered at a local level then more specificity may be required in terms of what they are being asked to deliver.